The causal impact of socio-emotional skills training on educational success - Giuseppe Sorrenti; Ulf Zölitz; Denis Ribeaud; Manuel Eisner (University of Zurich, Department of Economics, 2020)
We study the long-term effects of a randomized intervention targeting children's socio-emotional skills. The classroom-based intervention for primary school children has positive impacts that persist for over a decade. Treated children become more likely to complete academic high school and enroll in university. Two mechanisms drive these results. Treated children show fewer ADHD symptoms: they are less impulsive and less disruptive. They also attain higher grades, but they do not score higher on standardized tests. The long-term effects on educational attainment thus appear to be driven by changes in socio-emotional skills rather than cognitive skills.
Keywords: C93; I21; I24; I26; J24; 330; Socio-emotional skills; randomized intervention; child development; school tracking